Computed tomography-based virtual simulation versus ultrasound-based clinical setup in electron breast boost radiotherapy: Methodology for CT-based electron virtual simulation. (November 2019) - Serban, Monica; Lambert, Christine; Ruo, Russell; Maietta, Ciro; Parker, William; Evans, Michael; Hijal, Tarek
Highlights: Methodology for electron CT-based virtual simulation and target delineation. Includes methodology for virtual collision detection between patient and electron applicator. The methodology in its entirety has been implemented and clinically used. Quantifies dosimetric differences between the clinical setup using U/S-delineated target and CT-based simulation. Abstract: Purpose: To compare clinical setup using ultrasound (U/S)-delineated target versus computed tomography (CT) virtual simulation using CT-outlined target in breast electron boost. To describe a methodology for electron virtual simulation and collision testing with the treatment planning system (TPS). Methods: The two techniques were compared in a prospective study on 12 patients, who were treated using a clinical setup. Target definition was performed by both U/S and CT imaging. The U/S-based target was made visible on CT images by placing a radio-opaque wire on U/S skin markings. The dose distribution of the clinical setup was reproduced in the TPS using the actual electron patient treatment parameters. A CT-based TPS virtual simulation/dose optimization was compared to the clinical setup technique. Results: Mean beam aperture was larger by 16.3 cm 2 (p = 0.011) for U/S compared to CT-outlined target. Target mean depth difference (CT minus U/S) was 0.03 cm (p = 0.875). Target coverage at depth was adequate in all cases with CT-based simulation while under/overcovering the target at depth by more than 5 mm in 2 out of 12 cases with clinical setup. Mean target V90% was 98.5% (CT-based simulation) and 84.4% (clinical setup). Ipsilateral lung/breast were better spared with CT-based simulation. To date, the methodology for CT virtual simulation was applied on 152 patients and collision was avoided in all cases. Conclusions: CT-based simulation and target delineation allows for improved definition of the en-face electron field with less amount of normal tissue irradiated while including the entire target with an adequate margin and optimal electron energy.